2004
DOI: 10.1093/aob/mch073
|View full text |Cite
|
Sign up to set email alerts
|

Comparative ITS and AFLP Analysis of Diploid Cardamine (Brassicaceae) Taxa from Closely Related Polyploid Complexes

Abstract: The lack of supported hierarchical structure suggests that extensive reticulate evolution between these groups, even at the diploid level, has occurred (although an alternative explanation, namely ancestral polymorphism in ITS data, cannot be completely excluded). Several implications for the investigation of the polyploid complexes of concern are drawn. When tracing origins of polyploid taxa, a much more complex scenario should be expected, taking into account all relatives as potential parents, irrespective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 30 publications
3
39
0
Order By: Relevance
“…A systematic revision of P. crinita is therefore advisable. The presence of different ribotypes in the same genome has been frequently interpreted as an outcome of past reticulation events between divergent lineages either at the polyploid (Campbell & al., 1997;Vargas & al., 1999;Hodkinson & al., 2002;Yonemori & al., 2002) or diploid level (Wichman & al., 2002;Fuertes Aguilar & Nieto Feliner, 2003;Marhold & al., 2004). There is evidence suggesting that polymorphisms in Phlomis might be acquired by hybridization in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic revision of P. crinita is therefore advisable. The presence of different ribotypes in the same genome has been frequently interpreted as an outcome of past reticulation events between divergent lineages either at the polyploid (Campbell & al., 1997;Vargas & al., 1999;Hodkinson & al., 2002;Yonemori & al., 2002) or diploid level (Wichman & al., 2002;Fuertes Aguilar & Nieto Feliner, 2003;Marhold & al., 2004). There is evidence suggesting that polymorphisms in Phlomis might be acquired by hybridization in our study.…”
Section: Discussionmentioning
confidence: 99%
“…More problematic is the delimitation of taxa the evolutionary history of which involved extensive polyploidy, hybridization, and apomixis. Polyploidy and hybridization have been well documented in Draba (Brochmann 1992;Brochmann et al 1992 and references therein; Widmer and Baltisberger 1999a, b;Koch and Al-Shehbaz 2002;Scheen et al 2002;Beilstein and Windham 2003;Grundt et al 2004), Cardamine (Neuffer and Janche 1997;Urbanska et al 1997;Franzke et al 1998;Franzke and Mummenhoff 1999;Franzke and Hurka 2000;Lihova´et al 2000;Bleeker et al 2002a;Marhold et al 2002aMarhold et al , 2002bMarhold et al , 2004, and Lepidium (Lee et al 2002;Mummenhoff et al 2001a, 2004 andreferences therein). It is likely that these two phenomena influenced the evolution of all major genera of the family.…”
Section: Problematic Groupsmentioning
confidence: 98%
“…Of particular interest in this study is the use of AFLP to generate data for phylogenetic studies. Although some researchers have suggested that AFLP data are inappropriate for phylogenetic applications (Hollingsworth and Ennos, 2004;Kosman and Leonard, 2005), several empirical studies have revealed tree-like properties in AFLP data sets, and AFLP data are increasingly being used to estimate phylogenies, including for very shallow radiations (e.g., Marhold et al, 2004;Sullivan et al, 2004;Koopman, 2005;Mendelson and Shaw, 2005;Spooner et al, 2005a;Albach, 2007;Kilian et al, 2007). Meudt and Clarke (2007) reviewed several conditions in which the AFLP technique can be ideal.…”
mentioning
confidence: 99%
“…ing the phylogeny of organisms such as plants for which other nuclear and organellar markers are often lacking, insufficiently variable, or even inappropriate (Després et al, 2003;Pelser et al, 2003;Marhold et al, 2004;Bensch andÅkesson, 2005;Tremetsberger et al, 2006;Pellmyr et al, 2007). AFLPs can also complement other marker systems (such as DNA sequencing markers) in a phylogenetic study by, for example, providing resolution in different parts of the tree (Després et al, 2003;Pelser et al, 2003;Marhold et al, 2004;Koopman, 2005;Spooner et al, 2005b).…”
mentioning
confidence: 99%
See 1 more Smart Citation